Sizing and Implementation of Photovoltaic Water Pumping System for Irrigation - Santosh S. Raghuwanshi; Vikas Khare (Institute of Advanced Engineering and Science, 2018)
Solar photovoltaic systems convert energy of light directly into electrical energy. This work presents, a process to compute the required size of the stand-alone solar photovoltaic generator based water pumping system for an existing area. In addition solar photovoltaic generator is connecting voltage source inverter fed vector controlled induction motor-pump system. Perturb and observe are used for harvesting maximum power of PV generator in between buck-boost DC converter and inverter system. In this paper system result is validated by fuzzy logic system and compare with variable frequency drives based PI controllers, driving motor-pump system. The operational performance at 60 m head, VFD based controllers in terms overshoot and setting time and also analysis performance of motor-pump set under different weather conditions. By assessment of system we find that speed and torque variation, overshoot and settling time is more with PI controller, Fuzzy logic controller (FLC) performance have dominance to VFD based PI controller.